Weight self-stigma and engagement among obese students in a physical education class - Zhang, Bao Gen; Qian, Xiao Fang (Frontiers in Psychology, 2022)
Background: This cross-sectional study investigates the mediating effects of basic psychological needs satisfaction and the moderating effects of teacher autonomy support among the psychological mechanism that weight self-stigma affects engagement among students with obesity in physical education class. Methods: This study includes 165 Chinese high school students with obesity (mean age,16.84 [±0.147] years), comprising 93 males (56.63%) and 72 females (43.63%), with a mean BMI of 30.453 (Standard Deviation [SD] = 2.426). Participants completed the Weight self-stigma questionnaire, basic psychological needs satisfaction questionnaire, teacher autonomy support questionnaire and student engagement questionnaire. Results: Weight self-stigma and engagement among students with obesity was mediated by basic psychological needs satisfaction. The mediated effect of basic psychological needs satisfaction was moderated by teacher autonomy support. Conclusions: weight self-stigma and basic psychological needs satisfaction are the antecedents of influencing the engagement of students with obesity. weight self-stigma will not only directly block the engagement of students with obesity, but also indirectly block the engagement of students with obesity by hinder the acquisition of basic psychological needs satisfaction. Teacher autonomy support can lessen the negative impact of weight self-stigma on basic psychological needs satisfaction, and then significantly promote the engagement of students with obesity. Physical education teachers should focus on strengthening the application of autonomous support teaching strategies to help students with obesity meet their basic psychological needs satisfaction and promote their engagement in physical education.